Molecular epidemiology and genetic diversity of disappearing Plasmodium vivax in southern Thailand - Parsakorn Tapaopong; Gustavo da Silva; Aurel Holzschuh; Wasinee Rungsarityotin; Chayanut Suansomjit; Kanit Pumchuea; Khajohnpong Manopwisedjaroen; Amnat Khamsiriwatchara; Podjadeach Khuntong; Liwang Cui; Cristian Koepfli; Jetsumon Sattabongkot; et al. (Scientific Reports)
Abstract The evolution of genetic diversity and population structure of Plasmodium vivax as malaria elimination approaches remains unclear. This study analyzed the genetic variation and molecular epidemiology of P. vivax from Yala Province in southern Thailand, an area in the pre-elimination phase. Seventy P. vivax isolates, collected between 2017 and 2020, were genotyped for domain II of pvdbp and the 42-kDa region of pvmsp1 using amplicon deep sequencing. Data from Yala province were compared to published data from Tak province, where transmission was higher. Key analyses included nucleotide diversity (π), haplotype diversity (Hd), natural selection, recombination rates, and complexity of infection (COI). Genetic diversity in Yala was relatively low (π = 0.008dbp and 0.014msp1; Hd = 0.774dbp and 0.407msp1) compared to Tak (π = 0.012dbp and 0.027msp1; Hd = 0.849dbp and 0.962msp1). In Yala, polyclonal infections were found in 53.7% of pvdbp II and 47.8% of pvmsp1 42 isolates, with average COI of 1.6 and 1.7. Both genes were under balancing selection. Distinct genetic differences were found between Yala and Tak in pvmsp1 42 , providing a local genotypic profile useful for tracing parasite origins.